The Relationship Between Occupational Health and Safety Knowledge and Workplace Accidents - Tirta Amerta Isworo; Lujeng Galih Pradana; Muliadi; Hesti Jatmikowati; Lailatul Rahmawati; Tri Suryo Wibowo (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Work-related accidents and illnesses result in approximately 2.78 million deaths annually, accompanied by around 374 million non-fatal incidents that lead to prolonged absences, permanent disabilities, and significant economic losses. These figures reflect the immense global health burden borne by the labor sector, while underscoring the urgency of implementing comprehensive OHS systems across various industrial sectors. According to Heinrich’s theory, One of the dominant factors contributing to workplace accidents is workers’ knowledge regarding occupational health and safety. This indicates that workers who have a good understanding of occupational health and safety tend to exhibit safer work action and are better able to prevent workplace accidents. This study aims to analyze the association between occupational health and safety knowledge and workplace accident among workers at CV. X Banyuwangi. Method: This research used an Cross-sectional analytical study. 75 workers selected from 300 using simple random sampling, questionare-based data collection, and Chi-square analysis. The study findings revealed that the majority of respondents – 47 people (62,7%) from 75 selected workers  had insufficient knowledge. And 39 people (52%) reported having experienced a workplace accident within the past year.  Result:  of the Chi-square test showed a significant association between the level of occupational health and safety knowledge and workplace accidents (p <0.001), with a strong effect size (Cramer’s V = 0.80). Conclusion: Occupational health and safety knowledge was significantly associated with workplace accident history, but causal inference cannot be made due to the cross-sectional design